Manipulation of MWCNT Concentration in MWCNT/TiO2 Nanocomposite Thin Films for Dye-Sensitized Solar Cell - Huda Abdullah; Mohd Zikri Razali; Sahbudin Shaari; Mohd Raihan Taha (International Journal of Photoenergy)
Dye-sensitized solar cell (DSSC) using multiwalled carbon nanotube/titanium dioxide (MWCNT/TiO2) was successfully synthesized using sol-gel method. In this method, it has been performed under various acid treatments MWCNT concentration level at (a) 0.00 g, (b) 0.01 g, (c) 0.02 g, and (d) 0.03 g. Atomic force microscopy (AFM) was used to study surface roughness of the MWCNT/TiO2 thin films. The average roughness results for 0.00 g, 0.01 g, 0.02 g, and 0.03 g were 10.995, 18.308, 24.322, and 25.723 nm, respectively. High resolution transmission electron microscopy (HR-TEM) analysis showned the inner structural design of the MWCNT/TiO2 particles. The TiO2 nanoparticles covered almost all the area of MWCNT particles. Field emission scanning electron microscopy (FESEM) gave the morphological surface structure of the thin films. The thin films formed in good distribution with homogenous design. The DSSC with MWCNT/TiO2 electrode containing 0.03 g MWCNT were resulted in the highest efficiency of 2.80% with short-circuit current density Jsc of 9.42 mA/cm2 and open-circuit voltage Voc of 0.65 V.